2017
DOI: 10.1016/j.neuroimage.2016.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Using neuroimaging to help predict the onset of psychosis

Abstract: The aim of this review is to assess the potential for neuroimaging measures to facilitate prediction of the onset of psychosis. Research in this field has mainly involved people at 'ultra-high risk' (UHR) of psychosis, who have a very high risk of developing a psychotic disorder within a few years of presentation to mental health services.The review details the key findings and developments in this area to date, and examines the methodological and logistical challenges associated with making A C C E P T E D M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 111 publications
1
23
0
Order By: Relevance
“…As a key hub of the central executive network, the DLPFC plays a crucial role in working memory . Recently, cross‐sectional neuroimaging studies suggested that the prefrontal cortex was the site with the most robust abnormalities in UHR subjects and patients with schizophrenia . Reduced connectivity between the right inferior frontal gyrus and right posterior hippocampus was described in UHR subjects relative to healthy controls in a cross‐sectional study using delayed matching to sample task .…”
Section: Discussionmentioning
confidence: 99%
“…As a key hub of the central executive network, the DLPFC plays a crucial role in working memory . Recently, cross‐sectional neuroimaging studies suggested that the prefrontal cortex was the site with the most robust abnormalities in UHR subjects and patients with schizophrenia . Reduced connectivity between the right inferior frontal gyrus and right posterior hippocampus was described in UHR subjects relative to healthy controls in a cross‐sectional study using delayed matching to sample task .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a series of MRI-based discrimination analyses by Koutsouleris et al [163][164][165] has suggested the feasibility of identifying individuals at the highest risk of developing psychosis using neuroanatomical patterns (especially cortical and subcortical volumes) at the single-subject level. Given the significant differences between the ARMS-P and -NP groups, also in the gross morphologic features (e.g., sulcogyral pattern), 20,118,119 functional neuroimaging data, 22,43 and event-related potentials (e.g., mismatch negativity), [166][167][168] it may be expected that the combination of potential biological predictive markers 169 in addition to clinical predictors, such as a high level of depression, cognitive impairments, poor functioning and negative symptoms, 170,171 enhances accuracy in the prediction of psychosis onset in the clinical setting. 172 However, it should be noted that the ARMS is a heterogeneous concept not only in the context of its outcome (i.e., later psychosis onset) but also for inclusion criteria.…”
Section: Early Interventionmentioning
confidence: 99%
“…Considering that clinical CHR instruments alone detect only about 47% of transitions after 3 years (14), efforts have been made to identify potential risk factors for psychosis in several symptomatological and biological readouts, or biomarkers, of the disorder (15) so that individualized prognostication may be enhanced. The presence of environmental adverse events (16), cognitive impairments (17), neuromorphological (18), and electrophysiological (19) and hematological (20) alterations, as well as resting-state (21) and task-related (22) neural activity and connectivity anomalies, has been consistently reported in people at risk for psychosis compared with healthy individuals. Some of these phenotypes have been associated with both disease course and transition to the overt disease (4).…”
mentioning
confidence: 99%